Unveiling End-users' Satisfaction and Actual Use of Blockchain in e-Health: Empirical Evidence from Bangladesh - Begum, Ferdowsy; Khan, Rahat; Mandal, Jewel; Kaium, Md. Abdul; Rahman, Md. Shahinur; Zahan, Israt (Journal of Consumer Sciences, 2024)
Data safety and security have become threatening issues in the health industry. Against this backdrop, blockchain technology has opened up a new window for healthcare stakeholders. This research aims to enhance the understanding of the factors that influence user satisfaction and actual use behavior of blockchain technology in the electronic health sector in Bangladesh. A convenience sampling collected primary data (270 responses) from nurses, doctors, emergency staff, and laboratory technicians. AMOS and SPSS were used for analysis. The data were analyzed using descriptive statistics, assessing normality, common method bias, validity, reliability test and regression weight analysis. The findings of this study reveal that the task characteristics, performance expectancy, information quality, and service quality of blockchain are significantly related to end-user satisfaction. Performance expectancy had the greatest weighted influence on satisfaction. End-user satisfaction reflects strong usage behavior towards blockchain technology in Bangladesh. Surprisingly, system quality does not substantially affect user satisfaction derived from blockchain technology. This study analyzes the most critical predictors of satisfaction evoked by using blockchain, particularly relevant to the context of Least Developed Countries (LDCs), such as Bangladesh. To our knowledge, limited studies have yet examined user satisfaction and actual use behavior through the lens of IS success, Task Technology Fit (TTF), and UTAUT models in Bangladesh's e-health sector. This study is anticipated to provide an opportunity for additional investigation into the potential uses of blockchain in the medical field and other commercial sectors.